Stylistic Analysis of the Song Lyrics at the Album "30" by Adele: English - Sekoni, Rocky Paulus; Malelak , Deby M.; Bria , Gunter J. (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
This study analysis the figurative language used in the album's song lyrics Adele “30”. The songwriter plays with words and language to create power attractiveness and uniqueness of the song lyrics. Figurative language has the ability to more impact on readers. This study aims to answer two research problems, namely: (1) To identify the types of figurative language used in the lyrics of Adele's album track "30". (2) Analysis the meaning of language allusion contained in the lyrics of Adele's album song “30”. Data analysis based on figurative language theory put forward by Xu Youzhi (2005) and the theory of meaning put forward by Rozakis (1995). The results of this study shows that there are 5 types of figurative language found in Adele's album “30”. They are simile, personification, metaphor, hyperbole, irony, and. This study found (1 simile, 10 personifications, 4 metaphors, 7 hyperboles, 1 irony). And vice versa in analysing the meaning contextual research found several types of meaning used in song lyrics, namely the stylistic figurative language.